Comparative analysis of motorcycle utilization and frorecasting model of motorcycle ownership of Eastern Asian countries. - Leong, Lee Vien (2005)
In Malaysia, vehicles composition registered annually consists mainly of passenger cars, motorcycles, buses, medium and heavy lorries and almost 50% of the vehicles registered are motorcycles.